Plantago major in Traditional Persian Medicine and modern phytotherapy: a narrative review - Najafian, Younes (Electron Physician, 2018)
Plantago major has been used widely since ancient times, to manage a wide range of diseases including constipation, coughs and wounds. The aim of this study is to review the traditional application, botanical characterization, pharmacological activities, phytochemistry effects and toxicity of Plantago major. In this review study, medicinal properties of Plantago major are collected from credible pharmacopeias, textbooks of traditional Persian medicine (TPM) belonging to the 10–18th century AD, such as “The Canon of Medicine”, “Makhzan-Al- Advia” and so on. Moreover, electronic databases including Scopus, Medline and Web of science were explored for this purpose. Plantago major has been prescribed in various forms such as roasted seeds, decoction, syrup, liniment, gargle, rectal enema, vaginal suppository, eye and nasal drop for each illness by TPM scholars. Some of its traditional properties including wound healing, antipyretic, antitussive, anti-infective, anti-hemorrhagic, anti-inflammatory, diuretic, laxative, astringent and hemostatic have been confirmed in recent researches. Phytochemical investigations showed that Plantago major contains volatile compounds, triterpenoids, phenolic acids and flavonoids. Modern pharmacological studies have proven some of the traditional applications of Plantago major. Nevertheless, more investigations are required on this plant, because it has the potential to be used to produce various natural medications.